2020
DOI: 10.1186/s12889-020-08747-w
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity of school-age children in El Salvador according to two international systems: a population-based multilevel and spatial analysis

Abstract: Background: The World Health Organization (WHO-2007) and the International Obesity Task Force (IOTF-Cole) systems assess child weight status. However, derived estimations often differ. We aimed to a) compare the prevalence of overweight and obesity, b) analyze individual and contextual factors associated with child weight using multilevel analysis and c) explore the spatial distribution of overweight and obesity using both classification systems. Methods: We used data from the 2015/2016 National School Height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…El RNPT al ser un censo es de los pocos sistemas útiles para el diagnóstico, monitoreo y vigilancia nutricional en población escolar mexicana (14). Su metodología ha sido probada anteriormente (56) y aplicada en diversos países (57). Con la cobertura alcanzada permite un análisis de desagregación mínima, válida y confiable.…”
Section: Discussionunclassified
“…El RNPT al ser un censo es de los pocos sistemas útiles para el diagnóstico, monitoreo y vigilancia nutricional en población escolar mexicana (14). Su metodología ha sido probada anteriormente (56) y aplicada en diversos países (57). Con la cobertura alcanzada permite un análisis de desagregación mínima, válida y confiable.…”
Section: Discussionunclassified
“…+Otro aspecto destacado es la variabilidad de las prevalencias según el criterio utilizado, que se debe a los diferentes puntos de corte establecidos para identificar los grupos con riesgo de morbimortalidad asociada al exceso de peso, así como a las diferentes poblaciones de referencia utilizadas para elaborar las curvas de crecimiento (26). La prevalencia del sobrepeso y, especialmente, de la obesidad según los estándares de la OMS es superior a la que muestran los criterios del IOTF y de Orbegozo, lo que también se ha constatado en otros estudios (27,28). Estas discrepancias deben considerarse al hacer comparaciones, siendo adecuado presentar los resultados bajo diferentes criterios.…”
Section: Discussionunclassified
“…51 From another perspective, in a study conducted in El Salvador by Pérez et al with children aged six to nine years, despite the strong agreement between the WHO and IOTF growth charts, the WHO growth reference classifies more overweight and obese children than the IOTF. 52 Overall, the CDC BMI-for-age growth charts underperformed for screenings of nutritional diagnoses than the growth charts by WHO and IOTF. However, there is still controversy as to which growth reference would be more appropriate for international use, especially for children from five years old and over.…”
Section: Lengthmentioning
confidence: 99%
“…Some authors argue that the WHO/2007 growth reference consists of a non-obese sample of children in the United States aged 1-24 years with data collected from 1963 to 1974, being a reference population that represents a healthier group and, therefore, more sensitive to diagnoses of overweight. 7,52 However, other authors argue that the use of a single population in the modeling of growth charts makes them not suitable for international use and, therefore, they suggest the application of IOTF growth charts, as they were developed by combining the most recent BMI data of children aged 2-18 years from six nationally representative surveys from 1963 to 1993. 11,52 Regarding the quality of the selected studies, it was considered excellent, with most studies classified as having good methodological quality, as shown in Figure 2.…”
Section: Lengthmentioning
confidence: 99%